Let’s Get Parents Ready for Their Initial IEP Meeting - Hammond, Helen; Ingalls, Lawrence (Journal of the American Academy of Special Education Professionals, 2017)
Parental participation in the initial Individual Education Program (IEP) meeting is a critical component of the process. Even though parents have rights to be equally involved in making decisions at the IEP meetings, frequently parents aren’t prepared to be equal members on the team with school personnel. This study focused on a preparation program for parents who were to be attending their child’s first IEP meeting. The research was conducted in three phases through an interview and training process with 298 parents. Phase one consisted of asking parents a series of questions on their knowledge and perceptions regarding the meeting. Phase two involved an intervention of preparing the parents for the meeting. Phase three entailed asking the initial set of questions from phase one to determine gains parents had made in knowledge and attitudes about the meeting. Results indicate parents benefited greatly from the preparation prior to the meeting.